Identification and Detection of ompW Gene in Vibro cholera Isolated From Raw Meat and Street Vended Food in Kuching, Sarawak - Becirona, Senga (Universiti Malaysia Sarawak, UNIMAS, 2010)
Vibrio cholerae is a pathogenic bacterium which causes cholera if ingested through consumption of contaminated food such as raw meat and street vended food. Outer membrane proteins of V.cholerae play an important role during infection and induction of host commonly to human. A study was carried out for the identification of V. cholerae and detection of ompW gene in V. cholerae. Gram-staining and series of biochemical tests were performed for the identification of the V. cholerae isolates. Biochemical test showed ambiguity results. In this study, PCR assay for the detection of ompW gene in V. cholerae involved 5 samples of raw meat and 19 samples of street vended food. OmpW gene was only detected in the positive control of V. cholerae while there was no detection of ompW in all of the samples. This study shows a low occurrence of V. cholerae meat and street vended food in Kuching, Sarawak. Further research on this pathogenic bacterium is needed to avoid infection due to the consumptive of contaminated food.